Insights for lifetime predictions of O-ring seals from five-year long-term aging tests. (September 2020) - Kömmling, Anja; Jaunich, Matthias; Goral, Milan; Wolff, Dietmar
Abstract: O-rings made of HNBR, EPDM and FKM were aged in the compressed and uncompressed state at 150 °C, 125 °C, 100 °C, 75 °C, 60 °C and 23 °C for aging times of up to five years. Hardness was measured and increased with aging time and temperature for HNBR and EPDM, but it remained practically constant for FKM. Indenter modulus measurements were performed on the lateral O-ring surface (that was free of DLO effects) to assess an influence of the compression during aging, but none was detected. The equilibrium compression set (CS) exhibited faster and stronger degradation than hardness and was used for lifetime predictions using the time-temperature superposition (TTS) principle. With an end-of-lifetime criterion of 70% CS, lifetimes of 4.5 years, 50 years and 526 years at 75 °C were estimated for HNBR, EPDM and FKM, respectively. The activation energies derived from an Arrhenius plot of the shift factors from the TTS were 85 kJ/mol, 99 kJ/mol and 78 kJ/mol for HNBR, EPDM and FKM, respectively, revealing that a higher activation energy does not necessarily mean that the material has a higher lifetime at lower temperatures. Furthermore, the measured lifetime of EPDM O-rings at 100 °C (5 years) was compared to that predicted on the basis of the lifetime at 150 °C as well as 125 °C using the corresponding shift factors. The error of the prediction was only ±4%. However, this precise prediction could only be achieved using the five-year long-term aging data. When using only data from aging times up to 0.5 years and 2 years, the lifetime of EPDM O-rings at 100 °C was underestimated by 31% and 22%, respectively. Highlights: Results from five-year aging tests with aging temperatures between 150 °C and 23 °C. Comparison of HNBR, EPDM and FKM aging behavior and activation energy. Investigation of the influence of compression during aging. Lifetime prediction using equilibrium compression set data and time-temperature superposition. Discussion of predicted and measured lifetimes from short- and long-term aging.